The relationship between organizational structure and market orientation: An empirical aproach - Tomás Cabello Cabello; María Ángeles Revilla Camacho; Manuela Vega Vázquez (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
This study analyzes different antecedents of market orientation and goes deeply into the analysis of the relationship between organizational structure and market orientation. The data for the empirical research comes from a sample of small firms belonging to the industrial sector in the geographical area of an economy of the south of Europe - the Andalusian economy. The study includes 85 correctly-completed questionnaires. The results confirm the effect of formalization, integration and centralization on the firms' marketing orientation, but they do not allow it to be stated that there is a relationship between firms' marketing orientation and complexity. The implication for management is the need to check the organizational structures in order for them not to slow down the introduction of market orientation.
Keywords: 650; Market Orientation; organizational structure; industrial business; intangible resources